What techniques and tactics should be taught in table tennis? - Xie, X.; Li, W.; Zhu, H. (Research Quarterly for Exercise and Sport, 2018)
Background/Purpose: Many university physical activity programs offer table tennis classes to students. To teach table tennis effectively, instructors shall possess the content knowledge of table tennis that are developmentally appropriate for college students at the beginning level. Content knowledge (CK) consists of Common Content Knowledge (CCK) and Specialized Content Knowledge (SCK; Ball, Thames & Phelps, 2008). Specifically, in sports and games, CCK consists of knowledge of the rules and etiquette and knowledge of techniques and tactics (Ward, 2009). SCK consists of knowledge of the instructional tasks and representation and knowledge of students` errors (Ward, 2009). The purpose of this study is to map out the techniques and tactics that are developmentally appropriate for college students at a beginning level. Method: Forty games including 54 college students who were identified as beginners (USATT Rating < 800) have been collected. 33 games were videotaped by the researchers from two resources: (a) University Recreation Center (N = 9), (b) Table Tennis Introductory Class (N = 24), with the rest of games from publically available online resources (N = 7). Four steps were used to identify the techniques and tactics to be taught. First, the authors developed a database which contained all the techniques and tactics in table tennis. Secondly, the authors coded all the videos and identified the initial lists of techniques and tactics based on the frequency of these techniques and tactics being used in game play. Third, the authors sent the initial list to five experts (sport pedagogy specialist, table tennis instructors and coaches) for further validation and comments. Lastly, the authors finalized the list. Analysis/Results: As a result, ten techniques and four tactics were suggested as the content to be taught in table tennis for college students at a beginning level. Ten techniques include (a) backhand drive, (b) one step, (c) forehand drive, (d) forehand flat service, (e) split step, (f) forehand sidespin service with backspin, (g) forehand smash, (h) shuffle step, (i) transitional step, and (j) backhand push. Tactics that shall be taught to college students at a beginning level are: (a) return the ball to the same placement during the rally, (b) vary the ball placement during the rally, (c) vary the ball placement of service, and (d) vary the spin of service. Conclusions: The findings indicated a developmentally appropriate list of content to teach table tennis to college students at a beginning level. This knowledge of developmentally appropriate content could help physical activity instructors to teach table tennis more effectively and facilitate students learning. (Contact: xie.469@osu.edu